Athletic trainers' Influence on National Collegiate Athletic Association Division I athletes' basic psychological needs during sport injury rehabilitation - Bejar, M. P.; Raabe, J.; Zakrajsek, R. A.; Fisher, L. A.; Clement, D. (Journal of Athletic Training, 2019)
Context: Athletic trainers (ATs) have indicated a desire to better understand the motivations of athletes during rehabilitation. Self-determination theory offers an ideal lens for conceptualizing the antecedents, mediators, and consequences of motivated behavior.